Smallholder Farmers Contribution to Food Production in Nigeria - Chiaka, Jeffrey Chiwuikem; Zhen, Lin; Yunfeng, Hu; Xiao, Yu; Muhirwa, Fabien; Lang, Tingting (Frontiers in Nutrition, 2022)
Several studies have shown that smallholder farmers produce most of the food in low-income and developing countries and form the backbone of the country’s food supply. This study examines the extent these smallholder farmers in Nigeria can put the country on the path to self-sufficiency and ensure satiety for household food consumption through their local production. The study also examines food production and their resulting yield based on crop production and harvested area, as well as the percentage of crops produced for food or other purposes. The results show that production of rice, sorghum, soybean, cassava, and yam is low; and their corresponding yields are declining, with the exception of maize, although the harvested area increased from 2015 to 2018. As it is, the findings are a clear indication of inadequate per capita food supply due to low food production, especially for cereals. The study suggests closing the yield gap specifically for cereals, limiting post-harvest losses, and finding a sustainable balance between the uses of major food crops for animal feed to reduce pressure on land resource use. The different states production performance requires special attention to harness the agricultural potential of each geopolitical zone. Lastly, dry-season cultivation should be encouraged through irrigation to enable harvesting two-times in a year. The study offers useful approaches to assess the contribution of local farmers to the food supply of a growing population and provides suggestions for the government, stakeholders, and the international community willing to collaborate and invest in the agricultural sector.